Attitude and Knowledge of Medical Negligence among General Population of Ahmedabad City, Gujarat - Mohammed Musaib M. Shaikh1 , Dushyantkumar Barot2 , Jayjeet Trivedi3 , R. S. Bhise4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study explored perspective and knowledge on medical negligence among the general population of Ahmedabad city. 500 Peoples voluntary participated in the study. Peoples were asked to respond anonymously to a structured questionnaire which dealt with their views, perception, knowledge and attitude toward medical negligence.In the present study, out of 500 participants, 69% were male,58.4% were aged between 21-40years & 56.8% were graduate & postgraduate. The majority of people have quite good knowledge about medical negligence, but less knowledge about legal proceedings regarding medical negligence. Educational seminar and awareness programs on this subject may helpful for them and for medical professionals also.